Actualization the existential meanings as a form of psychological intervention in crisis psychology - Borodulkina, Tetiana (Psychological Prospects Journal, 2022)
Purpose. Substantiation of the possibility of using the actualization of existential meanings as a form of psychological intervention in crisis psychology Methods. Theoretical analysis of the problem of actualization of existential meanings as a form of psychological intervention of the crisis psychology; systematization and classification the practical experience of working with meanings using metaphorical associative cards (MAC); single case analysis method. Results. Orientation to the inner being of a person, his spiritual component and existential meanings in psychological practice is important. One of the ways to the “Spiritual Self” of a person is the actualization of existential meanings and self-consciousness; and conscious work with meanings is a resource for a person when experiencing normative and non-normative crises. MAC are considered as one of the effective tools in working with existential meanings, among the variety of which specific sets are identified that are most suitable for working with the semantic sphere of a person and the spiritual component of his self-consciousness. The expediency of using the author’s MAC to actualize the existential meanings of "The hands Heavenly or Earthly" as a mindfulness practice and a form of psychological intervention in crisis psychology is substantiated. The guiding, actualizing function when working with these MAC is performed by questions of existential content that accompany the image on each card in the MAC "The hands Heavenly or Earthly". The author’s techniques for actualizing existential meanings using MAC are described. Specific individual cases on the actualization of existential meanings are analyzed based on the results of the implementation of the author’s techniques, confirming that when performing the proposed exercises, the attention of the participant in such work is directed to the Spiritual plane. Conclusions. Work with existential meanings is necessary and expedient at the final stages of overcoming a crisis state by a person. The prospect of further scientific research is to conduct an empirical study of the mechanism of actualization of existential meanings when working with the MAC of actualization the existential meanings "The hands Heavenly or Earthly".